Is synesthesia more common in patients with Asperger syndrome? - Neufeld, Janina; Roy, Mandy; Zapf, Antonia; Sinke, Christopher; Emrich, Hinderk M.; Prox-Vagedes, Vanessa; Dillo, Wolfgang; Zedler, Markus (Frontiers in Human Neuroscience, 2013)
There is increasing evidence from case reports that synaesthesia is more common in individuals with autism spectrum conditions (ASC). Further, genes related to synaesthesia have also been found to be linked to ASC and, similar to synaesthetes, individuals with ASC show altered brain connectivity and unusual brain activation during sensory processing. However, up to now a systematic investigation of whether synaesthesia is more common in ASC patients is missing. The aim of the current pilot study was to test this hypothesis by investigating a group of patients diagnosed with Asperger Syndrome (AS) using questionnaires and standard consistency tests in order to classify them as grapheme-colour synaesthetes. The results indicate that there are indeed many more grapheme-colour synaesthetes among AS patients. This finding is discussed in relation to different theories regarding the development of synaesthesia as well as altered sensory processing in autism.